Usucapião extrajudicial como forma de regularização fundiária - Pagnoncelli, Andrei (2017)
Extrajudicial usucapion is a recent legislative change aimed at the lessening of the jurisdiction of courts in order to contribute to the relief of the judiciary. Although extremely useful, it is not being widely applied. All the procedures of usucapion existing in Brazilian’s law are capable of being postulated through extrajudicial usucapion, because the Civil Procedure Code instituted a new procedural rite that will be analyzed by the registrar of real estate, without removing such possibility from the Judiciary Power, thus being the choice between one or the other an option of the originator of the request. The need for procedures that are citizen-friendlier and also contribute to the withdrawal of non-contentious cases of the Judiciary, makes the Legislative Power turn its attention with more persistence, since the benefit is double: to the citizen and to the Judiciary. In addition to the lessening of the jurisdiction, this paper brings the analysis focused on the requirements of usucapion. It concerns about the historical aspects of the ownership and origin of the term. It also analyzes the main possessory theories of Savigny and Ihering, as well as the contemporary possessory theories of Silvio Perozzi, Raymond Saleilles, and Antonio Hemandez Gil. This paper analyzes the elements of possession in order to understand the legislation’s reasons for possessory protection. It concerns about the juridical nature of possession, concluding that it is a fact, not a right. It also concerns about the right of property, seeking to understand its concepts, the purpose of protection and the social function of property. It makes an analysis of the characteristics of the property right over the subjects and the object of the property right. It analyzes the registry system to understand why Brazil has adopted the system of property acquisition derived from the Roman Law. Afterwards, it enters the study of usucapion, possession requirements ad usucapionem, the existing modalities, the requirement demands of each modality, to later analyze the institute of indirect judicial expropriation, or also known as private expropriation. Finally, it deals with lessening of the jurisdiction of courts, entering into the main topic that is extrajudicial usucapion. It deals with all the facilitating elements and the elements that make it difficult to apply this institute. With regard to the practical aspect, it deals with the requirements of the author's attorney-file, the requirements for the notarial certificate, and the requirements that involve the registrar's analysis of the property. At the end of the study, we concluded that extrajudicial misappropriation is an extremely valuable measure for land regularization, with great importance for social development and the application of public policies. In addition, ensuring a correct decision that gives the author the right without having to seek a decision by a magistrate makes the measure even more useful as it will help to unburden the Judiciary. It is a research carried out by the inductive methodology, with bibliographic procedure and documentary technique.